1996
DOI: 10.1161/01.atv.16.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Lipids in the Diet Accelerate the Development of Fatty Streaks in Cholesterol-Fed Rabbits

Abstract: Studies have indicated that oxidized lipoproteins may play a role in atherosclerosis. We have recently demonstrated that the levels of oxidized lipoproteins in the circulation can be directly correlated to the quantity of oxidized lipids in the diet. The present study tested the hypothesis that dietary oxidized lipids accelerate the development of atherosclerosis. For 12 to 14 weeks, 36 male New Zealand White rabbits were fed a low-cholesterol (0.25%) diet containing either 5% unoxidized corn oil (control diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 38 publications
4
67
1
1
Order By: Relevance
“…Several studies have demonstrated the adverse effects of oxidized dietary fats on human and experimental animals; namely, consumption of oxidized oil caused liver dysfunction (Hayam et al 1995;Owu et al 1998) and was responsible for development of fatty streaks (Staprans et al 1996;Hur et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the adverse effects of oxidized dietary fats on human and experimental animals; namely, consumption of oxidized oil caused liver dysfunction (Hayam et al 1995;Owu et al 1998) and was responsible for development of fatty streaks (Staprans et al 1996;Hur et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate comparison with our previous study, which demonstrated that oxidized fatty acids in the diet accelerate atherosclerosis, 7 in this study we used a similar experimental protocol. Twenty-six 10-to 11-week-old male New Zealand White rabbits (2 kg initial weight) were divided into two equal groups and were individually housed in stainless steel cages at the San Francisco Veterans Affairs Animal Housing.…”
Section: Animal Modelmentioning
confidence: 99%
“…5 Most importantly, we recently have demonstrated that oxidized lipids in the diet are atherogenic. 7 We have shown that feeding a diet enriched in oxidized fatty acids to cholesterol-fed rabbits resulted in a significant increase in fatty streak lesions in the aorta. These results demonstrate for the first time that diets containing oxidized fatty acids accelerate atherosclerotic lesions.…”
mentioning
confidence: 96%
“…Furthermore, cooking with vegetable oils rich in MUFA would be expected to result in lower levels of lipid oxidation products compared with oils rich in PUFA (Grootveld et al, 1998;Kritchevsky & Tepper, 1967). Vegetable oils rich in PUFA are vulnerable to oxidation during heating in air and diets rich in oxidised PUFA increase levels of lipid oxidation products in human chylomicrons (Staprans et al, 1999) and accelerate the development of experimental atherosclerosis (Staprans et al, 1996). Also, animal studies have indicated that secondary lipid oxidation products from PUFA-rich oils are absorbed from the gut and inhibit hepatic enzyme activities (Kanazawa & Ashida, 1991).…”
Section: Introductionmentioning
confidence: 99%